Preparasi Membran Selulosa Asetat untuk Penyaringan Nira Tebu - Sri Wahy Murni (Eksergi, 2010)
In the current  the sugar cane process, the liquid  sugar cane is  purified  by physical  and chemical processes that need much energy and  produce waste. Membrane  process separation is alternative way  for purifying it. In this research, membrane was  prepared from cellulose acetate by phase inversion method with acetone as a solvent and formamide as additive. The experiment was conducted  by varying  cellulose acetate concentration and  evaporation period. Cellulose aseatat, acetone and formamide with a particular composition is stirred for 3-4 hours until homogeneous. Mixture is then filled into the bottle and closed tightly and left for 1 day. Furthermore, the mold is poured on flat glass and evaporated during the allotted time. Matter and its lining membrane is inserted in a tub filled with water at a temperature 2oC for 5 minutes, the membrane was then dried..  Performance of  membrane  produced was tested  determination by  liquid sugar cane. The result of the experiment showed that the best weight ratio of cellulose acetate:acetone:formamide was and evaporation period were 12.5:5.2:3.5  and  45 second respectively; the  membrane produced have volumetric flux, rejection of  TSS and       permeation      of sucrose       were 6.1698 l/m2.hour, 91.12%  and   89% respectively.